2020
DOI: 10.1111/jth.14981
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19: A collision of complement, coagulation and inflammatory pathways

Abstract: COVID‐19 is frequently accompanied by a hypercoagulable inflammatory state with microangiopathic pulmonary changes that can precede the diffuse alveolar damage characteristic of typical acute respiratory distress syndrome (ARDS) seen in other severe pathogenic infections. Parallels with systemic inflammatory disorders such as atypical hemolytic uremic syndrome (aHUS) have implicated the complement pathway in the pathogenesis of COVID‐19, and particularly the anaphylatoxins C3a and C5a released from cleavage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
133
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(136 citation statements)
references
References 72 publications
(151 reference statements)
1
133
0
2
Order By: Relevance
“…The overactivation of the complement cascade in the process of the inflammatory response by SARS-CoV-2 can lead to thrombosis (Fig. 4) [92,93]. Besides, due to the reduction of ACE2 proteins and a further increase in Ang II, enhanced BP can raise the occurrence of stroke.…”
Section: Strokementioning
confidence: 99%
“…The overactivation of the complement cascade in the process of the inflammatory response by SARS-CoV-2 can lead to thrombosis (Fig. 4) [92,93]. Besides, due to the reduction of ACE2 proteins and a further increase in Ang II, enhanced BP can raise the occurrence of stroke.…”
Section: Strokementioning
confidence: 99%
“…For patients compromised by the cytokine storm after COVID infection, the procoagulant state seems to be a common and important manifestation, affecting many organs, evolving to insufficiency of multiple organs. 2,3,6 As far as we know, this is the first report of prostate involvement in the context of COVID infection. SARS-CoV-2 was already found in semen, but which organ is affected by the infection is not yet clear.…”
mentioning
confidence: 67%
“…Polycarpou et al (120) suggested that targeting complement might contribute to reducing COVID-19 systemic complications (multiorgan failure, coagulopathy), mediated by lectin pathway activation. Therefore, inhibition of the complement system at the levels of C3 or C5a/ C5aR is considered a possible therapeutic option (121,122).…”
Section: Possible Associations Of Complement Activation Via the Lectimentioning
confidence: 99%